2019
DOI: 10.1037/vio0000225
|View full text |Cite
|
Sign up to set email alerts
|

A three-step gendered latent class analysis on dating victimization profiles.

Abstract: Objective: The purpose of this study was to identify patterns of teen dating victimization among boys and girls and examine their association with family and peer contextual risk factors and mental health indicators. Method: As part of the population-based Youths’ Romantic Relationships Project, 8,230 high school students, with a corresponding weighted sample of 6,531 teens, were questioned about their victimization experiences. In total, 2,022 girls and 1,245 boys reported having a romantic relationship in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 63 publications
(85 reference statements)
3
31
0
8
Order By: Relevance
“…In response to the first question, we found a four-class model for profiles that included varying levels of violence. The results echoed prior studies highlighting the plurality of TDV experiences in youth (Hébert et al, 2019). Results were consistent with the extant literature indicating that milder TDV is much more common than severe TDV (Choi et al, 2017;Haynie et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In response to the first question, we found a four-class model for profiles that included varying levels of violence. The results echoed prior studies highlighting the plurality of TDV experiences in youth (Hébert et al, 2019). Results were consistent with the extant literature indicating that milder TDV is much more common than severe TDV (Choi et al, 2017;Haynie et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…To the best of the authors' knowledge, this is the first study examining profiles of TDV among Chinese teens. Our results echo previous studies that highlight the utility of person-centered approaches for exploring the heterogeneity of TDV with Western samples (Choi et al, 2017;Goncy et al, 2017;Haynie et al, 2013;Hébert et al, 2019). Results revealed a high prevalence of TDV and suggest the need for effective intervention strategies to prevent TDV and address the needs of teen victims and perpetrators of TDV, particularly Severe/Multi-Type TDV.…”
Section: Np794supporting
confidence: 85%
See 1 more Smart Citation
“…In cases in which multiple types of DV victimization and perpetration (i.e., physical, verbal, and sexual) are accounted for, previous research has generally identified five classes [6,8,10]. These additional classes have included youth who are high on psychological/verbal violence but not the other types of DV [5,6,8,9,11], youth who report higher levels of victimization but not perpetration [7,8,11], youth who are high in perpetration but not victimization [8], and/or youth that report primarily sexual violence but not other types of DV [6,11].…”
mentioning
confidence: 99%
“…Adolescents who are victimized by peers or family members or who witness intimate partner violence within the family report more DV victimization and perpetration [12e14] likely because these experiences hinder an adolescent's capacity to develop the skills required to form and maintain healthy relationships. These predictors of DV differ based on the pattern of DV victimization and perpetration and across types of violence [5,6,8,9,11].…”
mentioning
confidence: 99%